LncRNA and mRNA expression profile of peripheral blood mononuclear cells in primary Sjögren’s syndrome patients - Peng, Yu; Luo, Xuan; Chen, Yingying; Peng, Linyi; Deng, Chuiwen; Fei, Yunyun; Zhang, Wen; Zhao, Yan (Scientific reports, 2020)
The aim of this study was to elucidate the expression profile and the potential role of long non-coding RNA (LncRNA) in the peripheral blood mononuclear cells of primary Sjögren’s syndrome (pSS) patients. RNA-seq technology was used to detect the differentially expressed LncRNAs and mRNAs between five age-and sex-matched paired pSS patients and healthy control PBMCs. The selected LncRNAs were detected in the validation study by RT-qPCR in 16 paired pSS patients and healthy controls. The GO, KEGG, co-localization, and co-expression analysis were performed to enrich the potential gene functions and pathways. In this study, 44 out of 1772 LncRNAs and 1034 out of 15,424 mRNAs were expressed differentially in the PBMCs of pSS patients. LINC00426, TPTEP1-202, CYTOR, NRIR, and BISPR were validated as aberrantly expressed, and these LncRNAs strongly correlated with disease activity of pSS. GO and KEGG pathway analysis revealed the significant enrichment of biological processes, cellular components, and molecular function of the up and down-regulated mRNAs, which were mainly concentrated in the immune response and immune system processes. Co-localization and co-expression analysis also revealed that differentially expressed LncRNAs in the PBMCs of pSS were strongly correlated to the mRNA functioning associated with immune response and cell metastasis. Numerous LncRNAs and mRNAs were found differentially expressed in the PBMCs of pSS patients, especially NRIR and BISPR; they interacted with the co-localized and co-expressed mRNAs, which might participate in the pathogenesis of pSS through the NF-κB, JAK-STAT, and other signaling pathways that regulate cell metastasis.